A quantitative method for analysing 3-D branching in embryonic kidneys: development of a technique and preliminary data - Fricout, Gabriel (Image analysis and stereology, 2002)
The normal human adult kidney contains between 300,000 and 1 million nephrons (the functional units of the kidney). Nephrons develop at the tips of the branching ureteric duct, and therefore ureteric duct branching morphogenesis is critical for normal kidney development. Current methods for analysing ureteric branching are mostly qualitative and those quantitative methods that do exist do not account for the 3dimensional (3D) shape of the ureteric "tree". We have developed a method for measuring the total length of the ureteric tree in 3D. This method is described and preliminary data are presented. The algorithm allows for performing a semi-automatic segmentation of a set of grey level confocal images and an automatic skeletonisation of theresulting binary object. Measurements of length are automatically obtained,and numbers of branch points are manually counted. The final representation can be reconstructed by means of 3D volume rendering software, providing a fully rotating 3D perspective of the skeletonised tree, making it possible to identify and accurately measure branch lengths. Preliminary data shows the total length estimates obtained with the technique to be highly reproducible. Repeat estimates of total tree length vary by just 12%. We will now use this technique to further define the growth of the ureteric tree in vitro, under both normal culture conditions, and in the presence of various levels of specific molecules suspected of regulating ureteric growth. The dataobtained will provide fundamental information on the development of renal architecture, as well as the regulation of nephron number.
Keywords: Kidney; Ledvica; Embryology; Slika, obdelava z računalnikom; Ureter; Mikroskopija konfokalna; Miši; Image processing, computer-assisted; ledvice; Mice; Microscopy, confocal; morfologija; patologija